Water Balance Effect of Urbanization and Countermeasures for Enhancing Urban Water Security Resilience - Qingfang Hu; Jianyun Zhang; Junliang Jin; Xiumin Chen; Xing Su (中国工程科学)
Over the past four decades, the rapid urbanization process in China, coupled with the impact of global climate change, has significantly affected the water balance in urban areas and their adjacent regions. This has led to prominent urban water issues such as floods, water scarcity, and water pollution, posing severe threats to the healthy development of cities. To address this, this study elaborates on the comprehensive effects of urbanization on water balance from six aspects: precipitation, evapotranspiration, runoff, groundwater, water quality, and water supply-demand balance. It analyzes the risks and challenges faced by urban water security in China under a changing environment and proposes basic principles, main ideas, and key strategies for achieving a healthy urban water balance and enhancing urban water security resilience. The study argues that to promote China's new urbanization, we should adhere to the principle of developing cities based on water availability and planning development according to water resources, proactively assess urban water security risks and their evolutionary trends, and strengthen proactive risk prevention. Additionally, it is necessary to actively optimize urban development and utilization patterns to promote smart urban growth, and strengthen coordinated governance of urban and watershed water issues to enhance the carrying capacity of urban water systems. Efforts should also be made to significantly improve urban emergency management capabilities to effectively respond to the impact of extreme meteorological and hydrological events, and actively promote the socialized management of urban water security risks to enhance adaptability and resilience. Finally, it is crucial to accelerate the resolution of key scientific and technological challenges in the field of urban water security.